2017
DOI: 10.13057/biodiv/d180116
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Coral reef lifeform variation around power plant activity: Case study on coastal area of Paiton Power Plant, East Java, Indonesia

Abstract: Abstract. Arbiastutie Y, Marsono Dj, Hartati MS, Purwanto R. 2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
1
3
0
3
Order By: Relevance
“…Acropora branching was found as the most abundant lifeform (23.09%) on the transect W102 located on the steep windward slope. This finding is in agreement with Suharsono (1996) and Saptarini (2017) reporting that the dominant coral species in a habitat depends on the environmental topology such as Acropora branching that usually lives on the reef slopes. Manuputty (1990Manuputty ( , 2008 states that the dominant branching coral colony in a reef is due to the quick recovery ability of Acropora spp.…”
Section: R E S U L T S a N D Discussion Ssupporting
confidence: 92%
“…Acropora branching was found as the most abundant lifeform (23.09%) on the transect W102 located on the steep windward slope. This finding is in agreement with Suharsono (1996) and Saptarini (2017) reporting that the dominant coral species in a habitat depends on the environmental topology such as Acropora branching that usually lives on the reef slopes. Manuputty (1990Manuputty ( , 2008 states that the dominant branching coral colony in a reef is due to the quick recovery ability of Acropora spp.…”
Section: R E S U L T S a N D Discussion Ssupporting
confidence: 92%
“…The differences in the life forms existing on small islands on either side or generally caused by factors such as temperature, water transparency, depth, and currents as well as the sensitivity degree of benthic life forms to environmental pressures which can also influence the growth rate, variation of lifeforms and coral reefs reproduction [21,22]. The research results of [23] on the Tunda Island, Banten Province, found the lifeforms groups analysis, based on the similarity index analysis among stations at different depths (shallow waters and deep waters) showed 4 groups had the most significant similarity in terms.…”
Section: The Similarity Of Habitats Conditions Among Stationsmentioning
confidence: 99%
“…Genus Porites memiliki tingkat ketahanan yang relatif tinggi pada faktor pembatas pertumbuhan dan perkembangannya . Pertumbuhan karang dipengaruhi oleh faktor lingkungan (Saptarini et al, 2017). Persentase tutupan karang keras berbeda antara dua kedalaman yang berbeda di mana perairan dangkal sebagian besar lebih tinggi daripada di perairan dalam (Fahlevy et al, 2017).…”
Section: Komposisi Dan Biodiversitas Komunitas Karangunclassified